Emerging biogenesis technologies of extracellular vesicles for tissue regenerative therapeutics - Jung-Hwan Lee; Ji-Young Yoon; Jun Hee Lee; Hae-Hyoung Lee; Jonathan C Knowles; Hae-Won Kim (Journal of Tissue Engineering, 2021)
Extracellular vesicles (EVs), including exosomes, carry the genetic packages of RNA, DNA, and proteins and are heavily involved in cell-cell communications and intracellular signalings. Therefore, EVs are spotlighted as therapeutic mediators for the treatment of injured and dysfunctional tissues as well as biomarkers for the detection of disease status and progress. Several key issues in EVs, including payload content and bioactivity, targeting and bio-imaging ability, and mass-production, need to be improved to enable effective therapeutics and clinical translation. For this, significant efforts have been made recently, including genetic modification, biomolecular and chemical treatment, application of physical/mechanical cues, and 3D cultures. Here we communicate those recent technological advances made mainly in the biogenesis process of EVs or at post-collection stages, which ultimately aimed to improve the therapeutic efficacy in tissue healing and disease curing and the possibility of clinical translation. This communication will help tissue engineers and biomaterial scientists design and produce EVs optimally for tissue regenerative therapeutics.